2020
DOI: 10.1186/s13287-020-01874-6
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stromal cells protect against vascular damage and depression-like behavior in mice surviving cerebral malaria

Abstract: Background: Malaria is one of the most critical global infectious diseases. Severe systemic inflammatory diseases, such as cerebral malaria, lead to the development of cognitive and behavioral alterations, such as learning disabilities and loss of memory capacity, as well as increased anxiety and depression. The consequences are profound and usually contribute to reduce the patient's quality of life. There are no therapies to treat the neurological sequelae of cerebral malaria. Mesenchymal stromal cells (MSCs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 65 publications
0
13
0
1
Order By: Relevance
“…A number of studies have already demonstrated that Plasmodium falciparum infection triggers long-term neurological deficits such as cognitive impairment, motor skills, visual acuity and seizures [ 59 , 60 ]. Events associated with inflammation and oxidative stress could also be related to these deficits [ 61 , 62 ]. In our work, we demonstrated, for the first time, that açai-enriched diet improved sensorimotor outcomes related to CM condition.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have already demonstrated that Plasmodium falciparum infection triggers long-term neurological deficits such as cognitive impairment, motor skills, visual acuity and seizures [ 59 , 60 ]. Events associated with inflammation and oxidative stress could also be related to these deficits [ 61 , 62 ]. In our work, we demonstrated, for the first time, that açai-enriched diet improved sensorimotor outcomes related to CM condition.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless and most important, specific neurological sequelae, including poor performance in balance beam test to evaluate motor coordination, are clearly present as sequelae after treatment of ECM (Dai et al, 2010;Reis et al, 2010). Cognitive deficits in multiple memory impairment (habituation, aversive and recognition memories) and behavioral alterations (depressive-like behavior) are also reported after CM (Reis et al, 2010;Lima et al, 2020). Some experimental murine models, non-susceptible to the development of experimental CM, are useful to reproduce severe forms of non-cerebral malaria, for instance: P. berghei NK65 infected C57BL/6 mice are used as an experimental model to investigate acute respiratory distress syndrome in malaria (Van Den Steen et al, 2010;Scaccabarozzi et al, 2018), while BALB/c mice infected with P. berghei ANKA compose a model of severe anemia and severe placental malaria (Neres et al, 2008;De Niz and Heussler, 2018).…”
Section: Neurocognitive and Behavioral Sequelae Of Severe Malariamentioning
confidence: 99%
“…Currently the neurocognitive impact of this approach on CM is being accessed in a clinical trial. Lima et al (2020) obtained promising results administrating mesenchymal stem cells (MSC) as adjuvant therapy to chloroquine at day 6 of infection, for ECM. Treatment with a single dose of MSC has protected infected mice against vascular damage and improved depressive-like behavior.…”
Section: Therapeutic Approaches To Neurocognitive and Behavioral Sequ...mentioning
confidence: 99%
“…Furthermore, through in vitro co-culture experiments, the authors detected that the presence of MSC induced reprogramming of microglia from M1 to M2 and decreased viral load, while increasing the expression of INF-α/β in Neuro2a cells [ 136 ]. Another set of pre-clinical studies also evaluated the efficacy of MSC in reducing depression in mouse models for Malaria [ 137 ], major depressive disorder [ 138 ] and chronic mild stress [ 139 ], all showing that MSC were able to dimmish depressive-like behaviors in the respective models. Interestingly, these studies proposed a common action mechanism of MSC that correlated with the microglial polarization from M1 to M2 phenotype, and down-regulation of TNF-α, IL-1β, and IL-6 (and MCP-1 in the last study).…”
Section: Msc: Multi-organ Protection Against Acute Injury?mentioning
confidence: 99%